Pill Politics : Drugs and the FDA - Ceccoli, Stephen J. (Lynne Rienner Publishers, 2022)
From aspirin to Viagra to the latest cancer treatment, the Food and Drug Administration acts as a gatekeeper determining what medicines are legally available in the United States. But in fulfilling that regulatory role, Stephen Ceccoli argues, the FDA may inadvertently be promoting new drugs at the expense of public health.The FDA's initial mandate to protect health grew out of pharmaceutical-related disasters in the early 1900s. Later criticisms that the agency's approach impeded industry competitiveness and failed to meet public need, however, led to a political compromise on its mission. The new FDA has cut its review time nearly in half and allows direct-to-consumer advertising, off-label promotion of drugs, and the "fast-tracking" of treatments. Ceccoli convincingly shows that this approval process, while redressing valid complaints, is also creating a new complex of problems that must be resolved.